K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 8 2016

=>3A= 3^2017-3^2016+3^2015-...-3^2+3

=>3A+A=4A=3^2017+1=>A=\(\frac{3^{2017}+1}{4}\)

B tương tự nha

Ta có: \(\dfrac{B}{A}=\dfrac{\dfrac{1}{2016}+\dfrac{2}{2015}+\dfrac{3}{2014}+...+\dfrac{2015}{2}+\dfrac{2016}{1}}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2017}}\)

\(=\dfrac{1+\left(1+\dfrac{2015}{2}\right)+\left(1+\dfrac{2014}{3}\right)+...+\left(1+\dfrac{2}{2015}\right)+\left(1+\dfrac{1}{2016}\right)}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2017}}\)

\(=\dfrac{\dfrac{2017}{2017}+\dfrac{2017}{2}+\dfrac{2017}{3}+...+\dfrac{2017}{2015}+\dfrac{2017}{2016}}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2017}}\)

\(=\dfrac{2017\left(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2015}+\dfrac{1}{2016}+\dfrac{1}{2017}\right)}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2015}+\dfrac{1}{2016}+\dfrac{1}{2017}}\)

\(=2017\)

29 tháng 3 2020

P(x) = x2016 - 2015x2015 - 2015x2014 - ... - 2015x2 - 2015x 

<=> P(x) = x2016 - 2016x2015 + x2015 - 2016x2014 + x2014 - ... - 2016x2 + x2 - 2016x + x 

<=> P(2016) = 20162016 - 2016.20162015 + 20162015 - 2016.20162014 + 20162014 -...- 2016.20162 + 20162 - 2016.2016 + 2016 

<=> P(2016)=20162016 - 20162016 + 20162015 - 20162015 + 20162014 - ... - 20163 + 20162 - 20162 + 2016

<=> P(2016) = 2016

Vậy P(2016) = 2016

29 tháng 3 2020

Ta có:

P(2016) = 20162016 - 2015 . 20162015 - 2015 . 20162014 -.....- 2015 . 20162 - 2015 . 2016 - 1

P(2016) = 20162016 - ( 2016 - 1 ) . 20162015 - ( 2016 -1 ) . 20162014 - ..... - ( 2016 - 1 ) . 20162 - ( 2016 - 1 ) . 2016 - 1

P(2016)= 20162016 - 20162016 + 20162015 - 20162015 + 20162014  - ..... - 20163 + 20162 - 20162 + 2016 - 1

P(2016) = 2016 - 1

P(2016) = 2015.

29 tháng 1 2020

\(B=2^{2016}-2^{2015}+2^{2014}-2^{2013}+.......+2^2-2^1+2^0\)

\(\Rightarrow2B=2^{2017}-2^{2016}+2^{2015}-2^{2014}+.........+2^3-2^2+2^1\)

\(\Rightarrow2B+B=3B=2^{2017}+2^0\)

\(\Rightarrow B=\frac{2^{2017}+2^0}{3}=\frac{2^{2017}+1}{3}\)

12 tháng 7 2019

Thay x = 2016 vào biểu thức B, ta có:

B = 20162016 - 2015.20162015 - 2015.20162014 - ... - 2015.20162 - 2015.2016 + 1

B = 20162016 - (2016 - 1).20162015 - (2016 - 1).20162014 - ... - (2016 - 1).20162 - (2016 - 1).2016 + 1

B = 20162016 - 20162016 + 20162015 - 20162015 + 20162014 - ... - 20163 + 20162 - 20162 + 2016 + 1

B = (20162016 - 20162016) + (20162015 - 20162015) + ... + (20162 - 20162) + (2016 + 1)

B = 2016 + 1 = 2017

Vậy ...